Characterization of Xylanase activity produced by Paenibacillus sp. XJ18 from TNBD Jambi, Indonesia - . KURRATAA’YUN; . YOPI; ANJA MERYANDINI (Bogor Agricultural University, Indonesia, 2015)
Lignocellulose waste in nature is increasing due to the increasing activity of agroforestry. Up to 40% of lignocellulose biomass are consisted of xylan. Xylan complete breakdown requires the action of xylanase. Xylanase has been used to breakdown xylan into commercial product such as low calories sugar, prebiotic, and biofuel. Due to its wide application, several variation of xylanase characterization are needed. Our previous studies have collected Paenibacillus sp. XJ18 from TNBD forest, Jambi, Indonesia, to gain a unique enzyme characteristic. In this study the characteristic of crude xylanase from Paenibacillus sp. XJ18 was investigated. The highest activity of xylanase production was at 36 h. The xylanase showed activity in a broad range of pH (4.5-9.0). The highest activity showed at pH 5.0, 90 oC. Crude enzyme extract was unstable and had halftime at its pH and optimum temperature about 67 min. The xylanase activity was increased about 4.59 times after being concentrated by 70% acetone (2.4578 U/mL). Based on TLC result, xylanase from Paenibacillus sp. XJ18 was predicted to produce xylobiose exclusively from extracted corncob xylan.